Cloning and expression of an adhesin (AIDA-I) involved in diffuse adherence of enteropathogenic Escherichia coli. - Benz, I (1989)
The adherence of enteropathogenic Escherichia coli (EPEC) to the small bowel mucosa is an important step in the pathogenesis of diarrheal diseases. It has been shown that many EPEC strains adhere to HEp-2 and especially HeLa cells in characteristic patterns termed localized adherence (LA) and diffuse adherence (DA). A plasmid-derived DNA fragment encoding a factor specific for LA hybridized only to EPEC strains expressing LA, which demonstrated that LA and DA are mediated by two genetically distinct adhesins. EPEC strain 2787 (O127:H27), isolated from a case of infantile diarrhea, exhibited three major properties: (i) it showed DA to HeLa cells, (ii) it carried two large (ca. 100-kilobase [kb]) plasmids and one small plasmid of about 3 kb, and (iii) no fimbriae could be detected by electron microscopy in organisms grown on agar plates or in liquid cultures. Whole isolated plasmid DNA was partially digested with EcoRI and cloned into the vector pBR322. One recombinant clone (pIB6) was found to exhibit the same DA pattern on HeLa cells as did the parent strain. This clone contained an 11-kb DNA fragment derived from the largest of the three plasmids, as shown by Southern hybridization. By deletion analysis, a 6.0-kb DNA fragment was shown to be sufficient for expression of the DA phenotype. This insert encoded the production of a 100,000-dalton protein mediating adhesion to HeLa cells.